Application of Fuzzy Delphi technique to identify the elements for designing and developing the e-PBM PI-poli module / Ahmad Fkrudin Mohamed Yusoff … [et al.] - Mohamed Yusoff, Ahmad Fkrudin; Hashim, Azmil; Muhamad, Norhisham; Wan Hamat, Wan Norina (Universiti Teknologi MARA, 2021)
Along with the wave of the Industrial Revolution 4.0 era, shifts in the aspects of approach in teaching and the integration of learning technology should always be given careful research and planning. Therefore, this study aims to see the elements needed to integrate technology and delivery strategies to design and develop an online problem-based learning module for the Islamic Studies course (e-PBM PI-Poli) in a polytechnic. The design of this study is a quantitative study using the Fuzzy Delphi technique. A questionnaire instrument was used to collect research data. Seventeen experts in educational technology, problem-based learning, Islamic studies, and curriculum participated in the study. Data analysis results showed that the experts accepted all these elements through the expert consensus value above 75%, the threshold value (d) ≤ 0.2, and the fuzzy score (A) ≥ α - cut value = 0.5. Therefore, it shows that these elements have gained expert consensus and are needed to design and develop the e-PBM PI-Poli module in Polytechnic. This research provides tremendous implications to the lecturers and students, and references Malaysia's education system to transform education through technology-based active learning.